Accelerated biogas production from lignocellulosic biomass after pre-treatment with Neocallimastix frontalis. (September 2018) - Dollhofer, Veronika; Dandikas, Vasilis; Dorn-In, Samart; Bauer, Christoph; Lebuhn, Michael; Bauer, Johann
Highlights: Hydrolytic pretreatment of hay for biogas production with Neocallimastix frontalis. Higher initial biogas production in variants treated with N. frontalis cultures. Increase of volatile fatty acids in variants treated with N. frontalis cultures. Accelerated fibre degradation in variants treated with N. frontalis cultures. Abstract: Two Neocallimastix frontalis strains, isolated from rumen fluid of a cow and of a chamois, were assessed for their ability to degrade lignocellulosic biomass. Two independent batch experiments were performed. Each experiment was split into two phases: hydrolysis phase and batch fermentation phase. The hydrolysis process during the N. frontalis incubation led to an initial increase of biogas production, an accelerated degradation of dry matter and an increased concentration of volatile fatty acids. As monitored by quantitative PCR, the applied N. frontalis strains were present and transcriptionally active during the hydrolysis phase but were fading during the batch fermentation phase. Thus, a separate hydrolytic pretreatment phase with anaerobic fungi, such as N. frontalis, represents a feasible strategy to improve biogas production from lignocellulosic substrates.